A Cross Sectional Study of Cardiopulmonary Complications and Severity of Pulmonary Hypertension and Lung Fibrosis in Patients With Systemic Sclerosis - Wan Ahmad Syahril Rozli WAN ALI,; Mohd Shahrir MOHAMED SAID,; Syahrul Sazliyana SHAHARIR,; Andrea Yu Lin BAN,; Rizuana Iqbal HUSSAIN,; Azmillah ROSMAN, (Archives of Rheumatology, 2015)
Objectives: This study aims to identify the characteristics of scleroderma patients in terms of sociodemographic and clinical characteristics and severity of lung fibrosis and pulmonary hypertension and to show the association between European Scleroderma Study Group (EScSG) scoring and severity of pulmonary hypertension and lung fibrosis. Patients and methods: This two center cross-sectional study included 43 scleroderma patients (4 males, 39 females; mean age 52 years; range 42 to 59 years) under clinical follow-up. Patients’ sociodemographic data were recorded. Median duration of illness was 10.0 years. All patients underwent blood tests, echocardiogram, full lung function test, six-minute walking test, and high resolution computed tomography of the thorax. Pulmonary hypertension was defined by echocardiogram as systolic pulmonary pressure >36 mmHg. Results: Limited systemic sclerosis was the predominant type (74.7%). Majority of high resolution computed tomography findings showed lung fibrosis with ground glass opacities (74.4%). Pulmonary hypertension was predominantly mild (31.7%), lung function test showed 36.1% restrictive lung disease, and a reduced diffusing capacity of the lungs for carbon monoxide (median 13.85) with reduced six-minute walking test distance (median 300.0 meters). Health Assessment Questionnaire scoring was predominantly in the mild to moderate disability group (median score of 0.5). Five patients (13.9%) had active disease based on the EScSG scoring. There were no significant associations between EScSG scoring and other clinical parameters. Conclusion: In our study, we found that scleroderma was predominant among females and the major type was limited systemic sclerosis. The lung function test revealed a sub-normal diffusing carbon monoxide with a reduced six-minute walking distance.